Functional voice skills for music therapists - Schwartz, Elizabeth (Elizabeth K.); Boyle, Sharon R.; Engen, Rebecca (Barcelona Publishers, 2018)
This thorough and informative book is designed to guide music therapy students, young clinicians, and educators in techniques for developing a rich, varied, engaging, and healthy clinical voice for use in music therapy practice. Because the voice is so individual and unique, the material leads each music therapist on a very personal journey of exploration and discovery. Through practical information and exercises readers will learn how to make the most of their own authentic voice, while maintaining good vocal health. Additional resources include a glossary of terms, worksheets for personalize.